Design and develop an optical setup related to the pump-probe technique for spectroscopic study (Baghdad Science Journal, 2024)
In this research, an optical system using Pump-Probe technology was designed to study the effect of changing the Frequency values, integration time, delay time, and laser pulse width on the pumping pulse energy on an arbitrary laser dye material with an absorption coefficient of about 650 nm. we found that decreasing the pumping time to 10% of the pulse time is not suitable for the pump-probe technique because there is no resonance between the pumping time and the detector response to the source used. Also, we indicate that increasing the pumping time to 20% of the pulse time results in the highest possible detector response at an integration time 150 μs in the pump-probe technique. therefore, we noted that the detector response becomes more suitable for working in the pump-probe technique as the pumping time increases, as well as the efficiency of the detector, which increases significantly as the pumping time increases, as well as the integration time for the same delay time, it is more stable at 20% pumping time and collection time 150 μs at a delay time of 12.4 ns.